(untitled) (E Global Congress, 2024)
This article explores the specialization of the judicial system in Uzbekistan from a historical perspective. Specialized courts—economic, administrative, criminal, and civil courts—are considered a significant component of the judicial-legal reforms in the country. The article analyzes the process of specialization within the judicial system, its historical stages, reforms, adopted legal norms, and the effectiveness of specialized courts. Additionally, it examines the achievements and challenges faced in enhancing the efficiency of court proceedings, protecting citizens’ rights, and establishing a fair judicial system through the introduction of specialized courts.